Live Streaming Strategy on TikTok Shop Media in Increasing Sales of Areta Wholesale Negligee - Fatma Lailatus Sabila; Riyan Andni (Journal of Social Science Utilizing Technology, 2023)
Background. In the advanced digital era, marketing and sales have significantly shifted towards social media platforms rather than the stock market due to the volatility of the stock market, which is very sensitive to issues. Therefore, one of the platforms that has caught the world's attention is TikTok, which is known for its short and creative content that dominates daily use. Purpose. This research was conducted with the aim of examining how the live streaming strategy on tiktokshop media increases sales of wholesale areta negligees. Method. This research was conducted through direct field research, besides that the research data source was obtained through primary data between sources and respondents directly, with a qualitative approach method. Results. Based on the results of interviews conducted by researchers, the increase in sales after using live streaming and TikTok Shop experienced a rapid increase before the application was available. Conclusion. The live streaming strategy on the TikTok Shop media platform has proven itself to be an effective tool for increasing sales of Areta Wholesale's negligee clothing products. With a creative and interactive approach, the business was able to capture the attention of potential audiences and cater to their preferences and needs. The live streaming feature allows direct interaction between the business and potential buyers, helping to answer questions, provide product explanations, and provide useful information. Adding value through live streaming content is key to building trust and a positive reputation in the eyes of potential customers. Collaboration with TikTok influencers has also proven effective in increasing product exposure and traction. Measuring and analysing the performance of the live streaming strategy is an important step to continuously improve sales results. Overall, the live streaming strategy on TikTok Shop is a great opportunity for Areta Grosir to get closer to potential buyers, create creative and informative content, and expand sales potential in the dynamic and innovative e-commerce era.